Myeloid-derived suppressor cells exacerbate poly(I:C)-induced lung inflammation in mice with renal injury and older mice - Xie, Zhiqi; Zhou, Haoyang; Obana, Masanori; Fujio, Yasushi; Okada, Naoki; Tachibana, Masashi (Frontiers in Immunology, 2023)
Viral pneumonia is a global health burden with a high mortality rate, especially in the elderly and in patients with underlying diseases. Recent studies have found that myeloid-derived suppressor cells (MDSCs) are abundant in these patient groups; however, their roles in the progression of viral pneumonia remain unclear. In this study, we observed a substantial increase in MDSCs in a mouse model of renal ischemia/reperfusion (I/R) injury and in older mice. When intranasal polyinosinic-polycytidylic acid (poly(I:C)) administration was used to mimic viral pneumonia, mice with renal I/R injury exhibited more severe lung inflammation than sham mice challenged with poly(I:C). In addition, MDSC depletion attenuated lung inflammation in mice with I/R injury. Similar results were obtained in older mice compared with those in young mice. Furthermore, adoptive transfer of in vitro-differentiated MDSCs exacerbated poly(I:C)-induced lung inflammation. Taken together, these experimental results suggest that the increased proportion of MDSCs in mice with renal I/R injury and in older mice exacerbates poly(I:C)-induced lung inflammation. These findings have important implications for the treatment and prevention of severe lung inflammation caused by viral pneumonia.